The combined method of rectocele treatment - A. M. Kuzminov; V. Yu. Korolik; Sh. T. Minbayev; L. P. Orlova; I. V. Zarodnyuk; O. Yu. Fomenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
Aim of investigation. To present experience of monitoring of 17 patients with 3-rd degree rectocele by clinical and instrumental tests in the early and remote postoperative periods. Studied patients underwent transrectal circular proctoplasty with plasty of rectovaginal septum by allotransplant.Key points. Operation was pathogenically proved, accompanied by long-lasting clinical effect, low rate of postoperative morbidity and reduces terms of rehabilitation of operated patients.Conclusion. Surgical technique, discussed in the article is efficient method of treatment of rectocele of the 3-rd degree.